Stock price effects and costs of secondary distributions - Mikkelson, Wayne H.; Partch, M.Megan (Journal of Financial Economics, 1985)
This study does not support the view that a large number of shares can be sold at the prevailing market price and at a small cost. A significant stock price decrease is observed at the initial announcement of secondary distributions. The price declines are greater for offerings by officers and directors and for larger offerings, but are significant for all types of sellers and for large and small offerings. There is no significant price decline at the offering when secondaries are announced in advance. Underwriting and other selling costs are substantial and are positively related to relative offering size.